Health Care for Homeless Women: Unmet Needs and Barriers to Care - Lewis, Joy H (Blackwell Science Inc, 2003)
OBJECTIVE: Homelessness is a significant and growing problem in the United States. Women and families are the fastest growing segments of the homeless population. Homelessness increases the risk of having health problems and encountering barriers to care. This study determines how much perceived unmet need for medical care there is among homeless women, what homeless women perceive to be barriers to health care, and how barriers and other factors are associated with unmet needs. DESIGN: Cross-sectional study of homeless women, utilizing structured interviews. SETTING AND PARTICIPANTS: Community-based probability sample of 974 homeless women aged 15 to 44 years. MAIN OUTCOME MEASURES: Perceived unmet need for medical care in the past 60 days. Relationship between unmet need and demographic variables, place of stay, source of health care, insurance, and perceived barriers to care. RESULTS: Of the 974 women, 37% reported unmet need for medical care. Controlling for other factors, the odds of unmet need were lower among those with a regular source of care (odds ratio [OR] to .35, 95% confidence interval [CI], .21 to 58), while having health insurance was not significantly associated. The odds of unmet need were higher among those who experienced the barriers: not knowing where to go (OR 2.27, 95% CI, 1.40 to 3.69), long office waiting times (OR 1.89, 95% CI 1.27 to 2.83) and being too sick to seek care (OR 2.03, 95% CI, 1.14 to 3.62). CONCLUSIONS: There is significant unmet need for medical care among homeless women. Having a regular source of care was more important than health insurance in lowering the odds of unmet need. Homeless women must be educated regarding sources of care, and clinics serving the homeless must decrease waiting times.